Structural and functional comparability study of anti-CD20 monoclonal antibody with reference product - Singh SK (Dove Medical Press, 2018)
Sanjay Kumar Singh, Santosh Pokalwar, Sandip Bose, Shivika Gupta, Suhani Almal, Ranjit Sudhakar Ranbhor Sun Pharmaceutical Industries Limited, Tandalja, Vadodara 390 012, India Background: Cell surface protein, CD20, is extensively expressed on the surface of B cells. Antibodies targeting CD20 protein are being used to treat B-cell malignancies and B-cell mediated autoimmune diseases. Considering the cost of therapy with innovator monoclonal antibodies for these diseases, development of biosimilar products for the treatment of such diseases provides affordable solution to rising healthcare costs. Materials and Methods: Reference products of rituximab (six batches) were procured and stored as per manufacturer's instructions. Cell lines used in bioassay were procured from American Type Culture Collection and all other reagents used for analysis were of analytical grade. Primary structure was studied by intact mass analysis, peptide fingerprinting, peptide mass fingerprinting and sequence coverage analysis. Higher order structure was studied by circular dichroism, ultraviolet-visible spectroscopy, fluorescence spectroscopy, and disulfide bridge analysis. Different isoforms of reference product and SB-02 were identified using capillary isoelectric focusing and capillary zone electrophoresis. Glycosylation was studied by N-glycan mapping using LC-ESI-MS, point of glycosylation, released glycan analysis using ultra performance liquid chromatography (UPLC). Product related impurities such as oligomer content analysis and oxidized impurities were studied using size exclusion chromatography and reverse phase high performance liquid chromatography, respectively.Results and Conclusion: Here, we report physicochemical and biological characterizations of Sun Pharma’s proposed biosimilar (SB-02) to rituximab, a monoclonal anti-CD20 antibody approved for the treatment of non-Hodgkin’s lymphoma and chronic lymphocytic leukemia. SB-02 and rituximab exhibited indistinguishable primary as well as higher-order structure upon analyzing with the array of analytical and extended characterization methods according to statistical methods. The molecule also displayed comparability to reference product in post-translational modifications and charge heterogeneity. In functional bioassays, SB-02 demonstrated comparable potency with respect to reference product. Our results indicate highly similar quality profile between SB-02 and rituximab. Keywords: biosimilar, rituximab, CD20, monoclonal antibody, Biosimilarity, ADCC, CDC